A Note on the Poly-Bernoulli Polynomials of the Second Kind. (21st November 2020) - Yun, Sang Jo; Park, Jin-Woo
Abstract : In this paper, we define the poly-Bernoulli polynomials of the second kind by using the polyexponential function and find some interesting identities of those polynomials. In addition, we define unipoly-Bernoulli polynomials of the second kind and study some properties of those polynomials.